COMPARATIVE RESULTS OF RECOVERY STAGE IN TWO-STEP TREATMENT OF MALIGNANT COLONIC OBSTRUCTION - V. I. Pomazkin (Вестник хирургии имени И.И. Грекова)
The aim of the study was a comparative analysis of results of different approaches to two-stage treatment of malignant colonic obstruction on the stage of recovery of the integrity of intestinal tract. The main group included 260 patients. A double-barreled colostomy was formed at the first stage, than resection of the colon with tumor removing and stoma excision were performed. The control group consisted of 192 patients. An obstructive resection of the colon was made at the first stage with following reconstructive operation. Intraoperative damage of the small intestine was observed in 6,9% patients of the main group and 18,2% patients of the control group. Postoperative mortality consisted of 1,2% in the main group and it was 1,5% in the control group. The early postoperative complications numbered 9,2% and 17,7%, respectively. The main risk factor of complication development was an expressed adhesion process of the abdominal cavity in the control group of patients. CONCLUSIONS. The method, which included the colostomy formation at the first stage with following radical surgery at the second stage, had advantages in case of elimination of malignant colonic obstruction.